International Migration And Development: A Bangladesh Perspective - Al Masud, Sheikh Mohammad Maniruzzaman; Rohana, Hamzah (Open Access Publishing Group, 2018)
Migration and development are closely associated issues for many years in the social studies because of their enormous socio-economic impacts both for the country of origin as well as the country of destination. It is as both an income maximization and risk minimization decision. International migration is a promising livelihood option for a developing country like Bangladesh which has myriad of development initiatives from migrants’ experiences and remittances. This review article provides a brief discussion on the diasporas’ movement, remittances and their contribution to socio-economic development of Bangladesh. International migration has contributed to the development of Bangladesh at the individual, community and national levels. Remittance has a significant effect on the welfare of migrants’ household as well as GDP, balance of payments and foreign exchange earnings of Bangladesh. It is greater than foreign aid and foreign direct investment (FDI). It should be ensured for appropriate utilization of migrants’ experiences for the micro and macro level development of Bangladesh, an emerging tiger of south Asia in the 21st century.